How do changes in oral health and chewing efficiency affect the changes of oral-health-related quality of life of nursing-home residents in the short term? - Zenthöfer, Andreas; Ehret, Judith; Zajac, Melania; Kilian, Samuel; Kostunov, Jana; Rammelsberg, Peter; Klotz, Anna-Luisa (Clinical interventions in aging, 2021)
Objective: To evaluate how changes in oral health and chewing efficiency affect the changes in oral-health-related quality of life (OHRQoL) of nursing-home residents over six months. Methods: The study was conducted in nine nursing homes. Sociodemographic and general data were collected for all eligible individuals (n = 150). Of these, 114 participants (mean age 82.0 [+/- 9.5] years, 77.2% women) were available for the following tests at baseline and six months later: a comprehensive examination of dental and general health, a two-colour mixing-ability test (to assess chewing efficiency), the Geriatric Oral Health Assessment Index (GOHAI; to evaluate the OHRQoL), and the Mini Mental State Examination (MMSE; to diagnose the presence and severity of dementia). Univariate and multivariate linear regression models were compiled to analyse possible factors affecting OHRQoL. Results: For the final analysis, 108 participants were available. For the study cohort as a whole, a decrease in the number of functional occluding pairs (C: 0.195; p = 0.034) and an increase in dental-treatment needs (C: -1.968; p = 0.056) had the greatest negative effects on OHRQoL as expressed by the GOHAI score. For denture wearers, a deterioration of denture condition (C: -2.946; p = 0.003) was the most important predictor for a decline in OHRQoL. Conclusion: A short-term decline in oral health and function affects the OHRQoL of nursing-home residents. The most important dental variables in this regard are the number of functional occluding pairs and dental and denture-related treatment needs.
Gesehen am 18.06.2021